Safety and effectiveness of central venous catheters usage in newborns intensive care unit - І. А. Anikin (Zaporožskij Medicinskij Žurnal)
To date, ensuring long-term venous access in newborns is an actual problem of intensive therapy. Central venous catheters, which implantable peripherally (PICC-line), are widely used as a medium-term vascular access in newborns in the department of intensive care.